Rhythmic auditory cueing in atypical parkinsonism: A pilot study - Alexander Pantelyat; Alexander Pantelyat; Gabriel Dayanim; Kyurim Kang; Kyurim Kang; Bela Turk; Ruben Pagkatipunan; Sera-Kim Huenergard; Albert Mears; Jee Bang (Frontiers in Neurology, 2022)
Rhythmic auditory cueing (RAC) can improve gait parameters in neurological disorders such as Parkinson's disease and stroke. However, there is a lack of research on the effects of RAC in patients with atypical parkinsonian disorders (APD). Using a smartphone metronome application, we aimed to investigate the immediate effects of RAC in patients with clinically diagnosed APD, namely Progressive Supranuclear Palsy (PSP-Richardson Syndrome and other variants, PSP-nonRS), Corticobasal Syndrome (CBS), Multiple System Atrophy (MSA), and Dementia with Lewy Bodies (DLB). A total of 46 APD participants (25 PSP, 9 CBS, 8 MSA and 4 DLB; age: mean = 70.17, standard deviation = 7.15) walked at their preferred pace for 2 min without any rhythmic auditory cueing (RAC). Participants then walked the same path for another 2 min with RAC set at a tempo 10% faster than the baseline cadence of each participant. After a 10–15-min break, participants walked the same path for another 2 min without RAC to observe for carryover effects. Gait parameters [cadence (steps/minute), gait velocity (meters/minute), and stride length (centimeters)] were collected at baseline, during RAC, and post-RAC. There was a significant improvement in cadence in all participants from baseline to during RAC and post-RAC (corrected p-values = 0.009 for both). Gait velocity also improved from baseline to during RAC and post-RAC in all participants, although this improvement was not significant after correcting for multiple comparisons. The changes in cadence and gait velocity were most pronounced in PSP. In addition, our exploratory analysis showed that the cadence in the suspected TAU group (PSP+CBS) showed a significant improvement from baseline to during RAC and post-RAC (corr. p-value = 0.004 for both). This pilot study using short-term RAC in APD patients demonstrated improvements in cadence and velocity. There is an urgent need for effective gait rehabilitation modalities for patients with APD, and rhythmic cueing can be a practical and useful intervention to improve their gait pattern.